The Influence of Work Capability, Innovative Work Behavior, and Internal Work Environment on Employee Performance at PTPN IV Regional II Kebun Limau Mungkur - Rizka Khairunnisya Br Sinaga; Wan Dian Safina; Suhaila Husna Samosir; Nur’ain Harahap (International Forum of Researchers and Lecturers, 2025)
The purpose of this research is to analyze and identify the influence of work capability, innovative work behavior, and internal work environment on employee performance at PTPN IV Regional II Kebun Limau Mungkur. This study involved 125 respondents, consisting of all employees of PTPN IV Regional II Kebun Limau Mungkur. The sample was determined using the Slovin formula, resulting in 95 participants in the survey. Data were collected through observation, documentation, interviews, and the distribution of questionnaires using a Likert scale. The methods used to analyze the data include classical assumption tests, validity and reliability tests. Data analysis was conducted using multiple linear regression through the SPSS program. The results of this study partially (t-test) prove that work capability has a positive and significant effect on employee performance at PTPN IV Regional II Kebun Limau Mungkur. Innovative work behavior has a positive and significant effect on employee performance at PTPN IV Regional II Kebun Limau Mungkur. The internal work environment also has a positive and significant effect on employee performance at PTPN IV Regional II Kebun Limau Mungkur. Additionally, work capability, innovative work behavior, and internal work environment simultaneously have a positive and significant effect on employee performance at PTPN IV Regional II Kebun Limau Mungkur, with an Fcount value (14.283) > Ftable (2.70), and a significance value of 0.000 < 0.05.